Decolonial knowledge in Practice: a mestiza reflection on sentipensar in indigenous Nasa epistemologies - Chaves Pérez, Paola (Frontiers in Sociology, 2025)
This paper presents the concept of sentipensar in the Nasa Indigenous practices. Through the concept of sentipensar this article shows that Nasa knowledge can emerge from being within relationships through the body, through affect, through intuition, and through deliberation processes that listen the body and the spirits. It affirms that knowledge is not only produced in the mind, but also in rituals, in land-based practices, and in the everyday acts of care and resistance that sustain community life. As such, sentipensar offers an understanding of knowledge that is deeply situated and communal, challenging the dominant view of knowledge as a cognitive or individual pursuit.